Exploitation of Information and Communication Technologies relating to the instruction of the subject of Modern Greek Language in Greek Junior High schools: Ideas and attitudes of teachers (philologists) - Paradia, Maria; Glavas, Sotirios; Mitsis, Napoleon; Kyriazis, Athanassios; Samaras, Haido; Aggelakos, Kostas (Παιδαγωγικά ρεύματα στο Αιγαίο, 2022)
Modern technologies have permeated all areas of human life, education being one of them. As in any wide-scale process, one has to consider the total extent of benefits it offers and difficulties it leads to; using the Information and Communication Technologies (ICT) for teaching and learning is no exception. A research team by members of the Greek Pedagogical Institute and the teaching staff of Greek Universities carried out a study in the academic year 2008-09 in the districts of Attica and Thessaloniki, concerning the subject of Modern Greek in Junior High schools (gymnasium). The purpose was to investigate the extent to which the affordances of ICT have been exploited during the instruction of Modern Greek in Junior High School (years 12-15) through the use of the new textbooks that include activities based on the integration of ICT. The present article describes the section of the research that was carried out with the aim of determining to which degree teachers (philologists) made use of these activities. The study also aimed at investigating their opinions and attitudes towards the use of ICT for the support of the Modern Greek Language course and their proposals for increased exploitation of ICT in this subject.